2021
DOI: 10.3892/ol.2021.12871
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glioma cells by antineoplastic activity of reversine

Abstract: Gliomas are the most common type of primary central nervous system tumors and despite great advances in understanding the molecular basis of the disease very few new therapies have been developed. Reversine, a synthetic purine analog, is a multikinase inhibitor that targets aurora kinase A (AURKA) and aurora kinase B (AURKB). In gliomas, a high expression of AURKA or AURKB is associated with a malignant phenotype and a poor prognosis. The present study investigated reversine-related cellular and molecular anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…In mouse, reversine-treated embryos upregulate the senescent markers p53 and p21 13 and thus fail to give rise to viable embryos 12 . Our results indicate that reversine also downregulates PARP1, as previously observed in glioma 60 . Thus, the effect of reversine on embryo development can be due to a combination of increase in DNA damage and downregulation of DNA repair.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In mouse, reversine-treated embryos upregulate the senescent markers p53 and p21 13 and thus fail to give rise to viable embryos 12 . Our results indicate that reversine also downregulates PARP1, as previously observed in glioma 60 . Thus, the effect of reversine on embryo development can be due to a combination of increase in DNA damage and downregulation of DNA repair.…”
Section: Discussionsupporting
confidence: 89%
“…Reversine-treated mouse embryos upregulate the senescent markers p53 and p21 (Singla et al, 2020) and fail to give rise to viable embryos (Bolton et al, 2016). Our results further indicate that reversine downregulates PARP1, as previously observed in glioma (Hirakata et al, 2021). Thus, reversine treatment may compromise embryo development due to a combined increase in DNA damage and decrease in DNA repair.…”
supporting
confidence: 78%
“…For example, Camk2 genes have been found to be strongly downregulated in GBM compared to the normal brain tissue (Johansson et al, 2005;Xiong et al, 2019;He and Li, 2021). Shc3 and kras are likewise downregulated in primary cultures and patient samples of GBM, while shc1, gadd45a and tgfbr2 are strongly upregulated (Magrassi et al, 2005;Lymbouridou et al, 2009;Guo et al, 2018;Hirakata et al, 2021). Moreover, the tumor suppressors pten and tp53 are frequently mutated and non-functional in GBM (Benitez et al, 2017;Zhang et al, 2018).…”
Section: Brain Regeneration Resembles Brain Cancer At Its Earlier Sta...mentioning
confidence: 99%
“…The double features of dedifferentiative and anti-tumor for reversine could be rationalized by its distinctive mechanism of action [9] , [10] . Recent studies have demonstrated that reversine can induce polyploidy, cell apoptosis and autophagy, and inhibit cell proliferation, invasion and metastasis, and it also exhibited significant cytotoxic effect on a variety of tumor cell lines in vitro [11] , [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%